Continuum modeling of park-and-ride services considering travel time reliability and heterogeneous commuters – A linear complementarity system approach - Du, Bo; Wang, David Z.W. (Transportation research. Part E, Logistics and transportation review, 2014)
•We model and solve the spatial equilibrium travel pattern in a linear travel corridor with continuous P&R facilities.•Heterogeneous commuters and travel time reliability are considered in model formulation.•Linear complementarity system approach is applied in model formulation.•Proof of solution existence of the model is provided.•Potential model applications are demonstrated. This paper studies the modeling of multimodal choice in a highway/railway system with continuum park-and-ride services along a corridor. Commuter heterogeneity and travel time uncertainty with correlation are considered, while both auto and rail transit are subject to congestion effects. Eventually, the equilibrium multimodal choice is modeled into a linear complementarity system and appropriate solution method is proposed to obtain the spatial equilibrium pattern along the corridor. Computational experiments are conducted to demonstrate the benefits of the proposed formulation and potential applications, such as optimization of park-and-ride facilities, development of land use policies to integrate urban development and transportation planning.